2010
DOI: 10.1007/s10562-010-0475-0
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Effect of Ce in Ce/OMS-2 Catalyst for Catalytic Combustion of Dimethyl Ether

Abstract: A new route to synthesize efficient Ce-doped manganese oxide octahedral molecular sieves (OMS-2) catalysts using birnessite precursor was developed. Their catalytic activities in the combustion of dimethyl ether (DME) were evaluated. N 2 adsorption, XRD, H 2 -TPR, O 2 -TPD and XPS techniques were employed in the catalyst characterization. A promoting effect of Ce in the Ce/OMS-2 catalysts on the catalytic activity was observed. For the most active sample with a Ce/Mn ratio of 0.07 (starting Ce/Mn molar ratio, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(28 citation statements)
references
References 41 publications
1
27
0
Order By: Relevance
“…Figure 6(a) displays the XPS spectra of Mn 2p and O 1s on the K-OMS-2 surface. The result revealed that Mn 2p spectra consisted of 641.96 and 643.85 eV, assigned to Mn 3+ and Mn 4+ species, respectively (Genuino et al 2013;Pan et al 2016;Sun et al 2017Tang et al 2010;Yu et al 2011). The Mn 2+ was not found from XPS spectra, corresponded to XANES results.…”
Section: Percent Removal Of Toluene =mentioning
confidence: 88%
See 1 more Smart Citation
“…Figure 6(a) displays the XPS spectra of Mn 2p and O 1s on the K-OMS-2 surface. The result revealed that Mn 2p spectra consisted of 641.96 and 643.85 eV, assigned to Mn 3+ and Mn 4+ species, respectively (Genuino et al 2013;Pan et al 2016;Sun et al 2017Tang et al 2010;Yu et al 2011). The Mn 2+ was not found from XPS spectra, corresponded to XANES results.…”
Section: Percent Removal Of Toluene =mentioning
confidence: 88%
“…The peak at lower binding energy, located at 529.57 eV was identified to the lattice oxygen. The peak at higher binding energy, located at 531.71 eV was associated with surface adsorbed oxygen, OH groups and oxygen vacancies (Dong et al 2017;Genuino et al 2013;Sun et al 2017Tang et al 2010;Xie et al 2016;Yu et al 2011). Nevertheless, the adsorbed molecular water species (O wat ) did not appear in the calcined K-OMS-2 samples, since K-OMS-2 samples were calcined at high temperature (200-600ºC), then the adsorbed molecular water species might lose during the synthetic method.…”
Section: Percent Removal Of Toluene =mentioning
confidence: 99%
“…The easier transportation, lower emission of polluting particles, and higher thermal efficiency of dimethyl ether (DME) make it a useful, low-cost replacement for liquefied petroleum gas (LPG) and diesel fuel. Recently, the catalytic combustion of DME has been studied on Cedoped manganese oxide octahedral molecular sieves (OMS-2) [9]. Mixed oxides with perovskite-type structures, in particular LaMnO 3.15 , have the potential to be highly active catalysts for the deep oxidation of DME.…”
Section: Dimethyl Ether (Dme) Combustionmentioning
confidence: 99%
“…The expected splitting energies of the 3s level are about 6.5 eV for Mn2+, 5.5 eV for Mn3+, and 4.5 eV for Mn4+ (Galakhov et al 2002;Wu et al 2006). The splitting energies on catalyst MnO x -350, MnO x -450 and MnO x -550 are about 5.15, Besides, the asymmetrical O 1s signal can be fitted with three components: one peak at low BE (about 529.7 eV), which is attributed to the lattice oxygen (O 2− ); another peak at the medium with a biding energy (531.1 eV) that is assigned to the surface adsorbed oxygen (O 2 − , O − , O 2 2− ) and the small peak at highest BE(533.0 eV) which is ascribed to the adsorbed OH groups and molecular water (Jirátová et al 2009;Puértolas et al 2013;Santos et al 2010;Yu et al 2011).…”
Section: Tpr Measurement and Xps Analysismentioning
confidence: 99%